Kecenderungan Neurotik, Relasi Dalam Keluarga Dan Penyesuaian Sosial Terhadap Resiliensi Penderita HIV Positif - Bayu Nugraha Murdiansyah (CV. Multi Kreasi Media, 2022)
The purpose of this study was to determine the relationship of neurotic tendencies, family relation and social adjustment to the resilience of HIV- positive patients. This study was quantitative study and used four variables. The instruments were used in this study are Neuroticsm Scale Questionnaire (NSQ), Index of Family Relations (IFR), Social Adjustment Scale-Self Report-Modified (SAS-M) and Resilience Scale (RS). The results showed that family relation contribute significantly to the neurotic tendencies, with the contribution 31.25 %. Family relation and neurotic tendencies simultaneously contribute significantly to resilience. Family relation directly affect resilience has contributed 10.43 %. Neurotic tendencies directly affect resilience has contributed 31.92 %. Family relation and neurotic tendencies directly affect resilience has contributed 62.7 % and the rest is influenced by other factors that can not be described in the study. Social adjustment variables have no direct influence on the resilience statistically